Anti-inflammatory mechanisms and pharmacological actions of phycocyanobilin in a mouse model of experimental autoimmune encephalomyelitis: A therapeutic promise for multiple sclerosis - Marín-Prida, Javier; Pavón-Fuentes, Nancy; Lagumersindez-Denis, Nielsen; Camacho-Rodríguez, Hanlet; García-Soca, Ana Margarita; Sarduy-Chávez, Rocío de la Caridad; Vieira, Érica Leandro Marciano; Carvalho-Tavares, Juliana; Falcón-Cama, Viviana; Fernández-Massó, Julio Raúl; Hernández-González, Ignacio; Martínez-Donato, Gillian; et al. (Frontiers in Immunology, 2022)
Cytokines, demyelination and neuroaxonal degeneration in the CNS play a relevant role in the pathophysiology of multiple sclerosis (MS) and its animal model of experimental autoimmune encephalomyelitis (EAE). Phycocyanobilin (PCB), the chromophore of the biliprotein C-Phycocyanin (C-PC) from Spirulina Platensis, has antioxidant, immunoregulatory and anti-inflammatory effects in this disease, and it could complement the effect of other Disease Modifying Treatments (DMT), such as Interferon-β (IFN-β). The purpose of this study was to demonstrate the effect of PCB in an animal model of chronic EAE. EAE was induced in C57BL6 female mice with the MOG35-55 peptide. Clinical signs, pro-inflammatory cytokines levels by ELISA, qPCR in the brain and immunohistochemistry using precursor/mature oligodendrocytes cells antibodies in the spinal cord, were assessed. PCB improved the clinical status of the animals, reduced the expression levels of brain IL-17 and IL-6 proinﬂammatory cytokines, in a dose-dependent manner. The down-regulation of genes LINGO1, NOTCH1, and TNFA, and an up-regulation of genes MAL, CXCL12, MOG, OLIG1, and NKX2-2 at the highest dose, were identified in the brain. Interestingly, a reduction of demyelination and microglial activation was detected with an increase in oligodendrocyte precursor cells and mature oligodendrocytes and a reduction in acute axonal damage in the spinal cord of PCB-treated EAE mice. Both the studies, in vitro in encephalitogenic cells and in vivo in the EAE model with the PCB/IFN-β combination, showed an enhanced effect of the combined therapy. These results demonstrate the anti-inflammatory and protective properties of PCB on myelin, and support its use with IFN-β in MS, thus having an impact on a pathway that targets myelin in demyelinating diseases.